2020
DOI: 10.3389/fnmol.2020.00047
|View full text |Cite
|
Sign up to set email alerts
|

Anterior Commissure Regulates Neuronal Activity of Amygdalae and Influences Locomotor Activity, Social Interaction and Fear Memory in Mice

Abstract: The two hemispheres of the vertebrate brain are connected through several commissures. Although the anterior commissure (AC) is the most conserved white matter structure in the brains of different vertebrates, its complete physiological functionality remains elusive. Since the AC is involved in the connection between two amygdalae and because amygdalae are critical for emotional behaviors and social interaction, we assessed amygdalar activity and function to investigate the physiological role of the AC. We fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 60 publications
0
9
0
1
Order By: Relevance
“…The anterior commissure's functional implications in humans are still somewhat elusive, appearing to be related to olfactory and non-visual interhemispheric communication (Gerrish et al, 2014). Studies on mice have found that the transection of this fascicle results in higher motor activity, aberrant social interaction and reduced associative memory, behavioral features associated with neuropsychiatric disorders, such as autism spectrum disorders (Hsu et al, 2020). The uncinate fasciculus is reported to contribute to reward/punishment based learning (Von Der Heide et al, 2013), facial emotional processing (Coad et al, 2017), emotional empathy (Oishi et al, 2015), and self-regulation (Passamonti et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The anterior commissure's functional implications in humans are still somewhat elusive, appearing to be related to olfactory and non-visual interhemispheric communication (Gerrish et al, 2014). Studies on mice have found that the transection of this fascicle results in higher motor activity, aberrant social interaction and reduced associative memory, behavioral features associated with neuropsychiatric disorders, such as autism spectrum disorders (Hsu et al, 2020). The uncinate fasciculus is reported to contribute to reward/punishment based learning (Von Der Heide et al, 2013), facial emotional processing (Coad et al, 2017), emotional empathy (Oishi et al, 2015), and self-regulation (Passamonti et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The highly coherent behavioral manifestations also lend a strong support for the imperativeness of delta oscillations, which serve as the basic or natural frequencies of the telencephalic networks. It is of note that MD, prelimbic cortex, and contralateral BLA ( Figure 7 ) are all telencephalic structures receiving direct glutamatergic input from left BLA ( McDonald, 1987 , Mátyás et al., 2014 , Hintiryan et al, 2019 ; Huang et al., 2019 ; Hsu et al., 2020 ). In contrast to the potential role of INs in local spreading (see above), PN probably is essential for distant or long-range projection of the oscillating activities.…”
Section: Discussionmentioning
confidence: 99%
“…An additional challenge will be determining whether ASD diagnosis can precede the therapeutic window in humans. Also, the effects of dietary zinc supplementation on neural circuits other than the thalamic-LA projection pathway such as the olfactory system and anterior commissure-related interhemispheric connectivity that have previously been shown to be dysfunctional in Tbr1 +/− mice [ 15 , 38 , 39 ], or those that may underlie ASD-associated behaviours observed in Tbr1 +/− mice (i.e. prefrontal cortex and ventral hippocampus for social memory and behaviours) require examination in future studies.…”
Section: Discussionmentioning
confidence: 99%